Entomopathogenic nematodes and their symbiotic bacteria: from genes to field uses - Tarasco, Eustachio; Fanelli, Elena; Salvemini, Carlo; El-Khoury, Yara; Troccoli, Alberto; Vovlas, Alessio; De Luca, Francesca (Frontiers in Insect Science, 2023)
The term “microbial control” has been used to describe the use of microbial pathogens (bacteria, viruses, or fungi) or entomopathogenic nematodes (EPNs) to control various insect pest populations. EPNs are among the best biocontrol agents, and major developments in their use have occurred in recent decades, with many surveys having been conducted all over the world to identify EPNs that may have potential in the management of insect pests. For nematodes, the term “entomopathogenic” means “causing disease to insects” and is mainly used in reference to the bacterial symbionts of Steinernema and Heterorhabditis (Xenorhabdus and Photorhabdus, respectively), which cause EPN infectivity. A compendium of our multiannual experiences on EPN surveys and on their collection, identification, characterization, and use in agro-forestry ecosystems is presented here to testify and demonstrate once again that biological control with EPNs is possible and offers many advantages over chemicals, such as end-user safety, minimal damage to natural enemies, and lack of environmental pollution, which are essential conditions for an advanced IPM strategy.